Structure-function relationships of chimeric antigen receptors in acute T cell responses to antigen. (October 2020) - Xu, Han; Hamburger, Agnes E.; Mock, Jee-Young; Wang, Xueyin; Martin, Aaron D.; Tokatlian, Talar; Oh, Julyun; Daris, Mark E.; Negri, Kathleen R.; Gabrelow, Grant B.; Wu, Ming Lun; Nampe, Daniel P.; et al.
Graphical abstract: Highlights: We compare 1221 chimeric antigen receptors (CARs) across 10 pMHC targets. The binding domain of CARs dominates their acute sensitivity. CARs tolerate change in other structural elements, e.g., the hinge and transmembrane domain. CAR binding avidity is weakly correlated with T cell acute response. The workhorse Jurkat/T2 cell model is a good surrogate for human primary T cell acute response. Abstract: Chimeric antigen receptors (CARs) and their parent signaling molecule, the T cell receptor (TCR), are fascinating proteins of increasing relevance to disease therapy. Here we use a collection of 1221 pMHC-directed CAR constructs representing 10 pMHC targets to study aspects of CAR structure-activity relationships (SAR), with particular focus on the extracellular and transmembrane structural components. These experiments that involve pMHC targets whose number/cell can be manipulated by peptide dosing in vitro enable systematic analysis of the SAR of CARs in carefully controlled experimental situations (Harris and Kranz, 2016 ). We find that CARs tolerate a wide range of structural variation, with the ligand-binding domains (LBDs) dominating the SAR of CAR antigen sensitivity. Notwithstanding the critical role of the LBD, CAR antigen-binding on the cell surface, measured by pMHC tetramer staining, is not an effective predictor of functional sensitivity. These results have important implications for the design and testing of CARs aimed toward the clinic.